2019
DOI: 10.1037/edu0000341
|View full text |Cite
|
Sign up to set email alerts
|

Long-term trajectories of academic performance in the context of social disparities: Longitudinal findings from Switzerland.

Abstract: This study used a stratified random sample of classes in Zurich, Switzerland, comprising approximately 2,000 students whose academic performances in math and language were assessed across primary and lower secondary education. Based on this longitudinal data, the study investigated the association of social inequalities with the baseline of, and gains in, academic performance. The study focused on growing social disparities in academic performance during compulsory education, taking into account disparities in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 67 publications
(135 reference statements)
2
5
1
1
Order By: Relevance
“…Four different developmental trajectories of academic achievement for Chinese adolescents were identified: high‐positive growth, middle‐negative growth, low‐stable, and lowest‐stable. We did not find a low‐increasing trajectory (in which adolescents initially have low achievement but display a moderate or fast growth over time), and the lack of it was inconsistent with previous studies with western samples (e.g., Hao & Woo, 2012; Helbling, Tomasik, & Moser, 2019; Hodis, Meyer, McClure, Weir, & Walkey, 2011) but consistent with previous studies with Chinese children samples (Fu et al, 2016). In the Chinese school system, particularly in middle and high school, learning difficulty increases with grade level due to increased challenges and demands in the academic curriculum, class assignments, and academic examinations.…”
Section: Discussioncontrasting
confidence: 99%
“…Four different developmental trajectories of academic achievement for Chinese adolescents were identified: high‐positive growth, middle‐negative growth, low‐stable, and lowest‐stable. We did not find a low‐increasing trajectory (in which adolescents initially have low achievement but display a moderate or fast growth over time), and the lack of it was inconsistent with previous studies with western samples (e.g., Hao & Woo, 2012; Helbling, Tomasik, & Moser, 2019; Hodis, Meyer, McClure, Weir, & Walkey, 2011) but consistent with previous studies with Chinese children samples (Fu et al, 2016). In the Chinese school system, particularly in middle and high school, learning difficulty increases with grade level due to increased challenges and demands in the academic curriculum, class assignments, and academic examinations.…”
Section: Discussioncontrasting
confidence: 99%
“…This is because, if such a linear growth trajectory truly occurred, the students who were advantaged early on in their development (e.g., by an effective instructional intervention) would necessarily remain advantaged over time, because the constant linearity of their learning trajectory would keep them ahead of their peers. Indeed, recent work that utilized a nonlinear decelerating growth model found that achievement gaps among high-resourced and lower resourced students did not increase over time in mathematics (Helbling, Tomasik, & Moser, 2019; Mok, McInerney, Zhu, & Or, 2015). These findings allow for the possibility that, by specifying a growth model as linear and therefore assuming that student learning rates are constant across developmental time, researchers may be overestimating the learning capacity of socially dominant children who enter schooling with higher levels of mathematics knowledge on average, or who grow faster on average earlier on.…”
Section: Mathematical Development As a Nonlinear Trajectorymentioning
confidence: 99%
“…A plethora of empirical studies have suggested nonlinear developmental trajectories of children's academic achievement in various domains throughout childhood and adolescence (Aikens & Barbarin, 2008; Bloom, Hill, Black, & Lipsey, 2008; Cameron, Grimm, Steele, Castro‐Schilo, & Grissmer, 2015; Ding & Davison, 2005; Helbling, Tomasik, & Moser, 2019; Parrila, Aunola, Leskinen, Nurmi, & Kirby, 2005). The general trend of academic development for most children in many countries indicates steeper rise during earlier schooling and continued but relatively slower growth later into schooling.…”
Section: Introductionmentioning
confidence: 99%
“…The general trend of academic development for most children in many countries indicates steeper rise during earlier schooling and continued but relatively slower growth later into schooling. However, researchers also found great individual differences in children's academic development, including both the starting levels and the changing patterns of their academic skills (Helbling et al., 2019; Wang et al., 2017). For example, children's initial academic levels and their growth rate were often found to be negatively or not significantly associated, suggesting initially low‐performing students to gradually catch up or not growing more slowly than their initially high‐performing peers (e.g., Ding & Davison, 2005; Parrila et al., 2005).…”
Section: Introductionmentioning
confidence: 99%